THE RELATIONSHIP OF LOYALTY AND WORK ENVIRONMENT TO ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) EMPLOYEES OF PT MIRAE ASSET SEKURITAS INDONESIA - Elisabeth Gracia Virluna Naku; Nenny Anggraini; Rutman Lumbantoruan (Fundamental Management Journal, 2024)
Organizational citizenship behavior (OCB) is an employee's actions to help coworkers outside of their core job. A decrease in OCB can result in a lack of loyalty and an insufficient and motivating job scope. The purpose of this research is to determine: (1) the relationship between employee loyalty and organizational citizenship behavior (OCB) of PT Mirae Asset Securitas Indonesia, (2) the relationship of work environment with organizational citizenship behavior (OCB) of PT Mirae Asset Securitas Indonesia employees, (3) PT Mirae The Relationship between Loyalty and Work Environment in Organizational Citizenship Behavior (OCB) of Employees in Asset Securitas Indonesia. This research uses quantitative methods. Data collection uses a questionnaire. Data analysis used Spearman rank correlation and multiple correlation. This research states (1) that there is a significant and positive relationship between loyalty to organizational citizenship behavior (OCB) of 0.559 and 0.000 <0.05. (2) Work environment and Organizational Citizenship Behavior (OCB) have a positive relationship of 0.337 and significant at 0.002 <0.05. (3) Organizational Citizenship Behavior (OCB) of 0.617 has a positive relationship between loyalty and work environment.